Blooket: A Teacher's Toolkit for Improving Students' Reading Comprehension and Vocabulary Mastery - Muharomah, Siti Anugrah; Hidayani, Selnistia; Perdana, Purnama Rika (Universitas Nurul Jadid, 2025)
Vocabulary mastery and reading comprehension are difficult for certain student. This conventional strategy has many drawbacks. Therefore, technology plays an important role in the scope of teaching and learning English as a Foreign Language (EFL). Engaging students' habits with their gadgets, particularly in the